Obtenção de dextrinas esterificadas e aplicação no processo de clarificação de cerveja - Gonçalves, Heloisa Morais (2018)
Clarifying agents are used in the manufacturing process of beer with finality to reduce the amount coloidal particulate and to obtain products limpid and bright. The aim of this study was to develop esterified dextrins from corn, potato and cassava starches by means of dextrinization process, in the presence of malic acid (2,5 – 10g.100g-1) under predetermined condition and applied in the worts for to evaluate the clarity power. The characterization of dextrins was accomplished through of analyses swelling power, solubility, paste clarity, Fourier transform mid infrared (FT-IR), amylose content, esterification percentage and scanning electron microscopy (SEM). The characterization of the worts was accomplished through proteins, phenolic components and clarity (absorbance 600nm). The analysis of the common dimension (ComDim) was performed through MATLAB software R2008b relating matrices and finding common dimensions that explain the correlation between the experiments. The modification propitiated higher percentage esterification, being observed in the FT-IR spectra by the appearance of bands in the region 1730 cm-1 , characteristics of esters groups. The dextrinization also caused lower amylose content, increase of swelling power, increase of solubility, increase paste clarity and fragmentation of the starches granules as observed by MEV. The clarifying effect of the dextrins was observed through reduction of proteins content and increase of clarity. Of all the dextrins, those of potato were that presented better performance, similar to carrageenan. It is concluded that the dextrins are an alternative for the clarification of the craft beer.